2019
DOI: 10.1039/c8cp07795a
|View full text |Cite
|
Sign up to set email alerts
|

On the large apparent Stokes shift of phthalimides

Abstract: The photophysics of N-methylphthalimide (MP) in solution (cyclohexane, ethanol, acetonitrile, and water) was characterized by steady state as well as time resolved fluorescence and absorption spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Femtosecond transient absorption : In order to get an idea about the efficiencies associated with the individual competing excited state reactions and their temperature dependence, femtosecond transient absorption measurements of the porphyrin‐trityl compounds as well as their building blocks were performed in toluene at room temperature and in isotropic frozen 2‐methyltetrahydrofuran solution at 85 K. Details on the sample preparation, experimental setup [33] and data treatment can be found in the Supporting Information. Since the observations for the investigated porphyrin‐trityl compounds were qualitatively very similar, only the results obtained for ZnTPP‐trityl and its building blocks are presented in the main text, while the corresponding data for the free base analogue are shown in the Supporting Information (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Femtosecond transient absorption : In order to get an idea about the efficiencies associated with the individual competing excited state reactions and their temperature dependence, femtosecond transient absorption measurements of the porphyrin‐trityl compounds as well as their building blocks were performed in toluene at room temperature and in isotropic frozen 2‐methyltetrahydrofuran solution at 85 K. Details on the sample preparation, experimental setup [33] and data treatment can be found in the Supporting Information. Since the observations for the investigated porphyrin‐trityl compounds were qualitatively very similar, only the results obtained for ZnTPP‐trityl and its building blocks are presented in the main text, while the corresponding data for the free base analogue are shown in the Supporting Information (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The setup has been described in more detail elsewhere. [47][48][49][50] In brief, a Ti:sapphire laser amplier system (Coherent Libra) with a repetition rate of 1 kHz, a pulse duration of 100 fs and a wavelength of 800 nm was used as the pulse source. Part of its output was used to pump a TOPAS-White non-collinear optical parametric amplier tuned to deliver pulses peaking at 530 nm.…”
Section: Femtosecond Transient Absorptionmentioning
confidence: 99%
“…Previous studies demonstrated that the energy of S 1 state, which corresponds to the location of the intersection of the normalized absorption and fluorescence spectra, barely differs from the energy of the onset of the absorption. 61,62 Therefore, the use of the latter quantity is a good approximation (see Figs S13 and S14 in the ESI). The obtained values suggest that PET from the S 1 state of all phthalimides should be thermodynamically feasible except for amino derivative 6.…”
Section: Electrochemical Propertiesmentioning
confidence: 96%